Health Education Increase Self Care Activity and Decrease Anxiety among Women With Advanced Stage Cervical Cancer - Suparmi Suparmi; Dina Indrati; Rusmini Rusmini (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
Desain Research experiment quasi with pre and post test design group control. Sample size each group 18 respondents. Technics sampling used quota. The result showed both homogeneous group ( p0.005). There are difference of self care actifities and also anxiety by education health at group intervence ( p=0.000). Suggestion that is needed to improve giving information to client individually depend on the needs of patients.